1989
DOI: 10.1111/j.1365-2362.1989.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four orally administered analogues of prostaglandin E1 and E2 on glucose tolerance and on the secretion of pancreatic and gastrointestinal hormones in man

Abstract: Oral glucose tolerance tests (75 g, 300 ml) were performed in 12 healthy volunteers, with prior administration of placebo, misoprostol (400 micrograms), rioprostil (300 micrograms), enprostil (70 micrograms), or nocloprost (200 micrograms), in a double-blind, randomized manner. None of the drugs significantly affected glucose tolerance, although with misoprostal some volunteers displayed an impaired glucose tolerance. Nocloprost was without effect on gastric inhibitory polypeptide (GIP) and did not influence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…While some reports describe an inhibition of insulin and GIP [37], others have found the converse [38] or no change in insulin, but a decrease in GIP [39]. Decreased GIP levels have recently been reported after misoprostol administration to human volunteers [40], No significant effects on insulin or GIP were ob served in the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…While some reports describe an inhibition of insulin and GIP [37], others have found the converse [38] or no change in insulin, but a decrease in GIP [39]. Decreased GIP levels have recently been reported after misoprostol administration to human volunteers [40], No significant effects on insulin or GIP were ob served in the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…In vivo and in vitro immunoneutralization studies using antisera against different epitomes of GIP abolished only 20% to 50% of the incretin effect. 37,38 Further, it has been shown that the abolition of insulin release caused by an oral glucose load leaves the incretin effect nearly untouched, 39 raising even more doubt that GIP has an exclusive role in the enteroinsular axis. We found that motilin also stimulated the endogenous release of insulin in duodenectomized dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose tolerance Impaired glucose tolerance in some patients; reduced integrated incremental responses of gastric inhibitory polypeptide; delayed insulin and C-peptide responses; disrupted enteroinsular axis without significant overall reduction in integrated incremental responses. 174…”
Section: Resultsmentioning
confidence: 99%